Assessing Job PeAssessing Job Performance: Employers’ Feedback on Bachelor of Elementary Education Graduates of Nueva Ecija University of Science and Technologyrformance: Employers’ Feedback on Bachelor of Elementary Education Graduates of Nueva Ecija University of Science and Technology - Mariel R. Tapadera; Mary Jane L. Tomas; Darwin M. Andres; Mary Angelie A. Cabacungan; Angelica O. Cortez; Donna D. De Guzman; Diezabel V. Esguerra; Faith M. Cuevo; Ethel Joy V. Sebastian; Lea DC. Veloso (Journal of Education and Teaching (JET), 2024)
This study assesses the job performance of Nueva Ecija University of Science and Technology-College of Education (NEUST-COED) Bachelor of Elementary Education (BEEd) graduates in both public and private schools. Conducted through surveys with 20 school administrators from selected elementary schools in Nueva Ecija, data was collected from July to December 2023 via Google Forms and Facebook Messenger. The study reveals high praise for NEUST-BEEd graduates, particularly in instructional competence and leadership skills. However, it suggests room for improvement in areas like research output and project development, specifically in publishing articles and contributing to journals. Recommendations include ongoing professional development, collaboration among graduates, and a focus on sustainability in research and project work. Overall, the findings affirm NEUST's BEEd program's effectiveness in preparing graduates for successful careers in education, advocating for continuous support and enhancement of their skills to meet the evolving demands of the field.